Philippine montmorillonite characterization and upgrading by flotation - De Yro, Persia Ada N. (2007)
Philippine bentonite deposits are impure Ca-type montmorillonite (MMT) which have limited applications. One of the biggest MMT source in the Philippines is bentonite mined from Barangay Homapon,Legaspi, Albay which is a nonswelling type and is composed of around 85% montmorillonite with impurities like quartz (such as cristoballite), feldspar, gypsum and traces of other non clay minerals. The study aims to establish a more effective way of upgrading Philippine bentonite by separating these impurities using flotation process. A parallel flotation study was conducted principally to investigate the response of two (2) collectors in separating the MMT from the bulk of impurities and vice versa. The collectors used were Lauryl Amine (cationic) and Sodium Dodecyl Sulfate (anionic). A 23 factorial experimental design was used to evaluate the effects of different collector dosage, frother (pine-oil) dosage and pH combinations. Flotation test products were characterized using X-ray Diffraction Analysis (XRD) and Firing Tests. Firing test involved the determination of water of plasticity, drying shrinkage and firing shrinkage of flotation products fired at 1000 degree Celsius, 1100 degree Celsius and 1200 degree Celsius. The samples identified to have the best possible separation were analyzed with Fourier Transform Infrared Spectrophotometer (FTIR) and Scanning Electron Microscopy (SEM) analysis to verify the best flotation results. XRD data analysis showed probable separation of montmorillonite and cristobalite in the samples treated with the following conditions using Lauryl Amine as the collector: (a) 0.06 ml collector dosage, 0.04ml frotherdDosage at pH 10; (b) 0.06 ml collector dosage, 0.08ml frother dosage and pH4; (c) 0.06 ml collector dosage, 0.04ml frother dosage and pH 4 and (d) 0.02 ml collector dosage, 0.04 ml frother dosage and pH 4. There was also separation in the samples treated with Sodium Dodecyl Sulfate with the following parameters:(a) 0.06 ml collector dosage, 0.08 ml frother dosage and pH 10, (b) 0.06 ml collector dosage, 0.04 ml frother dosage and pH 10, and (c) 0.02 ml collector dosage, 0.08 ml frother dosage and pH 4. Firing test results indicate that tails of the flotation products treated with Lauryl Amine at 0.06 ml collector dosage and 0.08 ml frother dosage had the most montmorillonite content since it had the highest firing shrinkage value. This further narrowed down the choices, leaving the samples treated with : (a) Sodium Dodecyl Sulfate at 0.06 ml collector dosage, 0.08 ml frother dosage and pH 10 and (b) Lauryl Amine at 0.06 ml collector dosage, 0.08 ml frother dosage and pH 4 samples as the parameters which successfully separated cristoballite from montmorillonite. These samples were tested further with FTIR and SEM to confirm the data obtained from XRD and firing test. FTIR spectrum data indicated that cristoballite went with the concentrate leaving montmorillonite as tails. This is confirmed further in the FTIR data where there is an increase in the H2O bending peak area. Results of SEM micrograph confirmed that cristoballite was separated from montmorillonite as shown by the presence of globular and rounded cristoballite minerals in the concentrate and flaky montmorillonite minerals in the tails. This study concludes that it is possible to obtain polymer grade montmorillonite from Philippine bentonite by flotation using Lauryl Amine with the following parameters: 0.06 ml collector dosage, 0.08 ml frother dosage and pH 4, X-ray Diffraction (XRD), Firing tests, Fourier Transform Infra-Red (FTIR) Spectrophotometer and Scanning Electron Microscope (SEM) analyses affirmed that flotation is a potential process to upgrade montmorillonite.
"March 2007."
Thesis (M.S. Materials Science and Engineering)--University of the Philippines Diliman.
Keywords: Montmorillonite -- Philippines; Flotation